“The most Important International Issue”: Belize, The British Empire, and the Post-War Foreign Policy of Guatemala (1945-1948) - Véliz Estrada, Rodrigo (2020)
In February 1948, a nearly military conflict broke out between Guatemala and the British Empire. The problem revolved around Belize in the context of the end of World War II when the British felt vulnerable. Thus, they overreacted to the active, though chaotic, strategy of the Guatemalan government to regain the territory. Great Britain sent troops and warships to Belize, in the midst of the United States' attempt to create an OAS with an anti-communist agenda. Declassified files from Great Britain, the United States, Mexico, and new personal letters from top Guatemalan officials help to recreate this forgotten and important moment of the early Cold War years in Latin America.